Investigating the Correlation Between Formal Tax Law Violations and the Manifestation of Tax Crimes in Batam, Indonesia - F Fetri; Rizki Tri Anugrah Bhakti; Dwi Afni Maileni (Journal of Science and Education (JSE), 2026)
This study examines how formal (administrative) tax non-compliance may, under specific legal and procedural conditions, escalate into tax crimes in Indonesia, using Batam as a case study. Batam is a free trade zone with intensive cross-border transactions and stringent VAT documentation requirements, making it a relevant setting for observing the administrative–criminal boundary in enforcement practice. Employing normative legal research, we analyze statutes and implementing regulations (including KUP provisions on Articles 38, 39, and 39A), OECD guidance as a comparative analytical lens and selected Indonesian court decisions (2020–2025) to map escalation thresholds and taxpayer safeguards consistent with the ultimum remedium principle. The findings suggest that formal violations, such as late or non-filing, deficient bookkeeping, and documentary irregularities, primarily serve as compliance-risk signals and should typically receive administrative attention. Criminal exposure becomes plausible only when these violations are accompanied by qualifying elements such as intent (dolus), patterned repetition, falsification/forgery, and demonstrable fiscal consequences supported by preliminary evidence procedures. Overly expansive criminalization may undermine legal certainty, taxpayer trust, and investor confidence. We recommend standardizing escalation indicators, strengthening the consistency of preliminary evidence assessment, and enhancing taxpayer legal literacy and administrative rectification pathways to ensure a fair and measurable boundary between administrative sanctions and criminal prosecution.